Christmas offering - Dimond, Elizabeth, Mrs. (Salt Lake City, UT : Project Gutenberg, 2020)
"Christmas Offering" by Mrs. Elizabeth Dimond is a collection of thoughtful poetry written during the mid-19th century. This work, characterized by its spiritual themes and reflections on creation, explores the beauty and significance of life through a Christian lens, highlighting the joy of existence and the importance of faith. The poetic expressions are deeply rooted in the values and sentiments typical of that era, focusing on personal devotion and the connection between humanity and the divine. The collection presents a series of poems, beginning with reflections on the creation story and the Garden of Eden, where Adam and Eve experience joy and tragic temptation. Dimond's verses capture the essence of divine creation, delineating the beauty of nature and the bond between God and humanity. Other poems range from heartfelt messages to loved ones, contemplations on home, and expressions of maternal love. Through vivid imagery and emotional depth, the poems convey profound insights about life, relationships, and the comfort of faith amidst life's challenges, inviting readers to appreciate the simplicity and grandeur of existence and the enduring nature of love and connection. (This is an automatically generated summary.)
Release date is 2020-12-21
Charlene Taylor, Chuck Greif and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive/American Libraries.)
Keywords: American poetry -- 19th century; Christian poetry, American